Theoretical and Methodological Approaches to the Supply Chain Strategies Role and Analysis of Seaport Competitiveness in the Far East of Russia - Elena V. Konvisarova; Tatiana A. Levchenko; Artem A. Pustovarov (International Journal of Supply Chain Management, 2019)
Under market conditions, competitiveness is the main quality of any subject, whether it is an enterprise or such a complex structure as a seaport. Competitiveness was considered by many authors abroad and in Russia from different positions: cost approach, innovative approach, supply chain. Each author endured a certain aspect as the main one for analysis. The article is based on the analysis of different points of view and study object features, substantiates the essence of competitiveness through an integrated approach, since the seaport, performing a complex of specific services, fights for demand at different levels: from international to intra-port. The aim of the study was the systematization of theoretical and methodological approaches to the analysis of seaport competitiveness in the Russian Far East for the further development of proposals on competitiveness improvement. Based on the analysis, they substantiated the significance of seaports in the modern world economy and the economy of the Russian Far East. They evaluated the development potential of the Far Eastern ports. On the basis of an integrated supply chain, the competitiveness of the seaports of the Far East of Russia was assessed.